Spatial and temporal distributions of polycyclic aromatic hydrocarbons in the Northern Arabian Gulf sediments. Issue 1 (15th November 2016) - Gevao, Bondi; Boyle, Edward A.; Carrasco, Gonzalo G.; Ghadban, Abdul Nabi; Zafar, Jamal; Bahloul, Majed
Abstract: Surficial sediment samples were collected from 25 locations within Kuwait Bay and outside the Bay, in the Northwestern Arabian Gulf, to access recent polycyclic aromatic hydrocarbon pollution in Kuwait. Time trends in the depositional history of PAHs to this portion of the Arabian Gulf was reconstructed from the analysis of a dated sediment core. Intersite differences in concentration exist although these differences were not statistically significant ( p  = 0.08). However, organic carbon normalized concentrations within Kuwait Bay were 4 times higher than the average concentrations outside the Bay and were shown to be statistically significant ( p  < 0.001). The sedimentary record showed that ΣPAHs concentration fluctuated between 12 and 25 ng g − 1 before 1970. Concentrations then increased sharply to a maximum of 45 ng g − 1 around the late 1970s and early 1980s followed by an exponential decrease in concentration to pre-1970 "background" concentrations of between 12 and 25 ng g − 1 . Highlights: Spatial mapping of PAH contamination showed higher concentrations in Kuwait Bay. The historical record of PAHs was reconstructed from sediment archives. The composition was dominated by the low molecular weight 3- and 4-ring PAHs. Sedimentary PAH concentrations peaked around the late 1970s and early 1980s. The concentrations of PAHs were low prior to the discovery of oil in Kuwait.